THE REFRACTION STATE OF THE PROFESSIONAL JUDGMENT AT A CONCEPTUAL LEVEL - Viorica Mirela STEFAN-DUICU (Challenges of the Knowledge Society, 2019)
The conceptual and material construction of the present article involves a high degree of originality and conceptual innovation, the ideas stated here are not to be found anywhere in this world as we know it and it represents the proof of dedication into research, of the will to be involved in the growth of the content and notions regarding the professional judgment. This article is centred on the description of the professional judgment taking into account its refraction state. In order to explain this posture we have used several concepts and took the following steps: defined the professional judgment, used the specific literature for widening the research area, used analogies and connections with other domains and finally placed the professional judgment in the current organizational environment and explained its refractivity state through the components and existing influence factors.